Pertumbuhan dan Produksi Jagung pada Berbagai Varietas dan Dosis Trichokompos - Abd. Rahman Arinong; Pratiwi Hamzah; Nurdin; Herland (Politeknik Pertanian Bogor, 2024)
The productivity of maize as a staple food needs continuous enhancement through various methods, one of which is fertilization. The exploration of diverse fertilizers is expected to help reducing the reliance on increasingly expensive synthetic fertilizers. Fertilization is a crucial practice to improve soil fertility on marginal lands. It refers to land with productivity limitations due to factors such as low soil fertility, poor soil texture, or environmental conditions that do not support optimal plant growth. By providing additional nutrients through trichocompost fertilizer, plants are expected to grow better even under suboptimal soil conditions. This study aims to investigate the effect of trichocompost fertilizer dosage on various maize varieties grown on marginal land. The research was conducted using an experimental design with plot sizes of 3 x 5 meters. The method employed was a factorial Randomized Block Design (RBD) with two factors. The first factor was the dosage of trichocompost (control, 3 tons/ha, and 6 tons/ha), and the second factor was maize varieties (Sinhas1, Nasa29, JH36, Bisi18, and Pioneer27), with each treatment repeated three times, resulting in a total of 45 experimental plots. The parameters tested included plant height, number of leaves, ear height, days to flowering, and fresh ear weight. The results showed that trichocompost had a significant effect on two parameters: the increase in plant height and the number of leaves at 49 days after planting (DAP), as well as the fresh ear weight. The maize variety significantly affected almost all tested parameters.